Learning orientation as mediator between international entrepreneurial orientation and international firm performance in global halal industry - Ismail, Mazida; Mohamad, Norhidayah; Ahamat, Amiruddin (Universiti Sultan Azlan Shah, 2023)
The halal industry has provided a new competitive advantage for Muslim countries, especially Malaysia, as the export of halal products is now one of the most important contributions to the national income. The contribution is mostly by small-medium enterprises (SMEs). However, in ensuring the sustainability of SMEs in the international market, the firm needs to hire managers with internationally oriented entrepreneurs to prepare SMEs to face uncertain environments globally through the intervention of learning orientation as an organizational culture. Thus, this research was conducted to examine the mediating effect of learning orientation between the international entrepreneurial orientation and international firm performance of SMEs in the global halal industry. This study is a quantitative, cross-sectional study. Purposive sampling was used as the sampling method where the sample was selected based on four criteria: SMEs, manufacturer, possession of a Malaysia halal certification, and exporter of halal products. Responses collected from 136 top management teams from participating firms were analyzed using PLS-SEM. The results show that the relationship between international entrepreneurial orientation with international firm performance is conditional upon learning orientation. To operate internationally, having managers equipped with prior entrepreneurial behavior is insufficient to increase performance. Learning orientation thus servesas a platform to transfer tacit knowledge to employees and at the same time value employees’ ideas so that continuous changes can take place. This improvement will ultimately result in higher international firm performance